PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KOPI BUBUK CANG ENG SPESIAL TALANG BENIH CURUP BENGKULU - Zainal Muttakin; Taufik Bustami (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2023)
This study aims to determine the effect of brand image and product quality on purchasing decisions of Cang Eng Special Talang Benih Curup Bengkulu Coffee Powder. This research was conducted on consumers of Cang Eng Special Powder Coffee Talang Curup Bengkulu, the population used in this study were all consumers who bought Cang Eng Special Powder Coffee Talang Curup Bengkulu. The number of samples used was 120 respondents. The data that has been collected is processed using the Classical Assumption Test Technique, Multiple Linear Regression Analysis Techniques, Analysis of the Coefficient of Determination (R2), and Partial Test (t test), Simultaneous Test (f test). The results of this study indicate that partially the brand image variable has a significant effect on the purchasing decision variable, H1 is accepted and product quality has a significant effect on the purchasing decision variable, H2 is accepted. Meanwhile, the f test of brand image (X1) and product quality (X2) have a significant influence on the purchasing decision (Y) of Cang Eng Special Talang Benih Curup Bengkulu Coffee so that H3 is accepted. The overall significant level is (sig Î± = 0.000 <0.05). As well as having a regression equation Y = 2.219 + 0.253X1 + 0.608X2. And the coefficient of determination (R2) for the value of R Square is 0.684. Where the coefficient of determination means that together Brand Image and Product Quality make a major contribution in influencing the Purchase Decision of Cang Eng Special Talang Curup Bengkulu Coffee Powder. And the most dominant factor with the largest regression coefficient value is the product quality variable (X2) with a value of 0.608. Keywords: Brand image, Product Quality, And Purchase Decision